Health(y) education: A critical analysis of the role of public health regulation in and on tertiary education in Aotearoa New Zealand. Issue 7 (November 2021) - Shaw, Susan; Tudor, Keith
This article offers a critical analysis of the role of public health regulation on tertiary education in Aotearoa New Zealand and, specifically, the requirements and processes of Responsible Authorities under the Health Practitioners Competence Assurance Act for the accreditation and monitoring of educational institutions and their curricula (degrees, courses of studies, or programmes). It identifies and discusses a number of issues concerned with the requirements of such accreditation and monitoring, including, administrative requirements and costs, structural requirements, and the implications for educational design. Concerns with the processes of these procedures, namely the lack of educational expertise on the part of the Responsible Authorities, and certain manifested power dynamics are also highlighted. Finally, the article draws conclusions for changing policy and practice.